Membrane Restructuring by Bordetella pertussis Adenylate Cyclase Toxin, a Member of the RTX Toxin Family - Martín, César (American Society for Microbiology, 2004)
Adenylate cyclase toxin (ACT) is secreted by Bordetella pertussis, the bacterium causing whooping cough. ACT is a member of the RTX (repeats in toxin) family of toxins, and like other members in the family, it may bind cell membranes and cause disruption of the permeability barrier, leading to efflux of cell contents. The present paper summarizes studies performed on cell and model membranes with the aim of understanding the mechanism of toxin insertion and membrane restructuring leading to release of contents. ACT does not necessarily require a protein receptor to bind the membrane bilayer, and this may explain its broad range of host cell types. In fact, red blood cells and liposomes (large unilamellar vesicles) display similar sensitivities to ACT. A varying liposomal bilayer composition leads to significant changes in ACT-induced membrane lysis, measured as efflux of fluorescent vesicle contents. Phosphatidylethanolamine (PE), a lipid that favors formation of nonlamellar (inverted hexagonal) phases, stimulated ACT-promoted efflux. Conversely, lysophosphatidylcholine, a micelle-forming lipid that opposes the formation of inverted nonlamellar phases, inhibited ACT-induced efflux in a dose-dependent manner and neutralized the stimulatory effect of PE. These results strongly suggest that ACT-induced efflux is mediated by transient inverted nonlamellar lipid structures. Cholesterol, a lipid that favors inverted nonlamellar phase formation and also increases the static order of phospholipid hydrocarbon chains, among other effects, also enhanced ACT-induced liposomal efflux. Moreover, the use of a recently developed fluorescence assay technique allowed the detection of trans-bilayer (flip-flop) lipid motion simultaneous with efflux. Lipid flip-flop further confirms the formation of transient nonlamellar lipid structures as a result of ACT insertion in bilayers.